Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Simulation Menggunakan PhET untuk Materi Medan Magnet - Hidayah, Nurul; Talakua, Prisilia; Azis, Dede Abdul; Maipauw, Musa Marsel (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to develop an interactive learning media based on Augmented Simulation using PhET for magnetic field material, with the goal of enhancing students' understanding of physics concepts that are difficult to grasp through conventional methods. The research method used is Research and Development (R&D), based on a 4D development model simplified into 3D (Define, Design, Develop). The results show that the developed media can accurately and interactively depict magnetic field phenomena, contributing to improved student understanding. The validation results from media and physics content experts indicate that this media meets curriculum standards and is effective in increasing student engagement. However, some aspects still need improvement, particularly in the functionality of feedback and the development of physics models in the simulation. The implications of this research are significant in the context of technology-based education, given the great potential of Augmented Simulation to enhance students' learning experiences.